(untitled) (Historia, 2021)
South African participation in the Korean War was a complex matter: militari ly and in terms of domestic and foreign politics. Nonetheless South Africa place d an air force squadron as well as a token army element at the disposal of the United Nations Forces, including a small medical section. This study focuses in on the transience of life of about 900 South African soldiers during war. Hedonis m, searches for light-hearted pleasure and making the most of the moment have always accompanied war. the Korean War was no different. Despite South African racial politics, the South African Korea contingent suffered a STD rate of some 130 per thousand per year.